THE EFFECT OF SAVING LOANS ON SERVICE REVENUE PERFORMANCE: (Study on groups of mothers in Bening RT: 02 and 03 RW: 01 Sutojayan Subdistrict) - Anisa Wahyu Lianing Fadhilah (Universitas Islam Balitar, 2018)
This study aims to determine how much influence savings and loans have on the performance of service income in the group of mothers. This study uses a quantitative descriptive method by conducting questionnaires on 56 respondents. The data analysis method used is a simple linear regression analysis that is assisted by SPSS version 24.0 for Windows.The results of the analysis show the effect of savings and loans on the performance of service income in the group of women, namely Y = 16.417 + 0.307X obtained by a constant of 16.4% with a regression coefficient of 30.7%. The results of the determination coefficient show 27.4%, which means that the savings and loans variable has a very low effect on the service income performance variable. Whereas through the test obtained tcount 2.093 greater than t table 2.003.